Indirect effects of theory of mind on alcohol use and problems in underage drinkers: The role of peer pressure to drink. (December 2022) - Kumar, Lakshmi; Zhou, Agnes; Sanov, Bethany; Beitler, Sara; Skrzynski, Carillon J.; Creswell, Kasey G.
Highlights: Youth with social deficits may consider alcohol a way to be accepted by peers. This may explain why such youth misuse alcohol. Indeed, indirect effects were found between low theory of mind on adverse alcohol through conformity motives. Findings highlight the role of social cognition in young adult alcohol misuse. Abstract: Objective: Prior studies demonstrate a link between socio-cognitive deficits and alcohol problems in adolescents and young adults. Researchers have proposed that young people with such deficits may misperceive and over-value peers' attitudes about drinking and consider drinking a way to be accepted by their peer group. We test this hypothesis by investigating whether theory of mind (ToM) deficits in underage (18–20-year-old) drinkers are associated with binge drinking and alcohol problems, and whether these ToM deficits have an indirect effect on alcohol outcomes through perceived peer pressure to drink (i.e., high conformity motives and low perceived ability to refuse alcohol during social pressure). Method: Participants ( N = 472; 91 % female; 71 % White; Mage = 19.28 ± 0.77) were recruited from TurkPrime and completed measures assessing ToM, conformity motives, self-efficacy to resist peer pressure to drink, alcohol problems, and binge drinking. Bivariate correlations were run to examine associations between study variables. Indirect effect models were run in SPSS, using the PROCESS add-on, to assess the indirect effects of ToM on alcohol outcomes through conformity motives and self-efficacy to refuse peer pressure to drink. Results: ToM had indirect effects on binge drinking and alcohol problems through conformity motives (but not self-efficacy to resist peer pressure to drink). Lower ToM was associated with higher conformity motives, which were then associated with more frequent binge drinking and greater alcohol problems. Conclusions: These findings highlight the role of social cognition in young adult alcohol misuse and suggest more work is needed to understand the potential influence of peer pressure in this association.